PENDIDIKAN BERBASIS KESETARAAN GENDER: Studi Kebijakan Pemerintah dan Aplikasinya dalam Pendidikan - Inayatul Ulya (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2013)
Abstract Gender equality-based education is education that accommodate gender differences. This study aims to reveal the gender sensitivity insocial and educational as well as identify government policies in building gender equ ality and its applications in formal education. This study is qualitative with an inventory of government policies in building gender equality, and then analyze it with the reality of education in Indonesia. The approach used in this study is referring to the normative approach to the study of government policies in enforcing gender equality and its applications in formal education. The research data was collected using the techniques of literary study (library research). Materials that have been acquired and processed is described and analyzed by using descriptive interpretative paradigm and gender analysis. Although many efforts have been taken by the government for the realization of gender equality, but in the education sector still  show gender inequality. The indication can be seen from three aspects, they are not unequal participation in education for women, unequal educational material as well as the selection of majors unequal proportions of men and women. The phenomenon is not yet reflect the totality of gender equality education. Keywords:pendidikan, kesetaraan gender, kebijakan pemerintah